Spin splitting and reemergence of charge compensation in monolayer WTe2 by 3d transition-metal adsorption12. Issue 11 (6th March 2017) - Song, Yan; Wang, Xiaocha; Mi, Wenbo
Abstract : Transition-metal adsorption effectively modifies the intrinsic properties of monolayer WTe2, where the electron–hole pockets reemerge with Ni adatom. Abstract : The semimetallic WTe2 has sparked intense interest owing to the non-saturating magnetoresistance, pressure-driven superconductivity and possession of type-II Weyl fermions. The unexpected and fascinating quantum properties are thought to be closely related to its delicate Fermi surface and a special electron–hole-pocket structure. However, in the single-layer limit, the electron–hole-pocket structure is missing owing to the lack of interlayer interaction. Herewith, we demonstrate that 3d transition-metal adsorption is an effective method to modify the electronic properties of monolayer WTe2 by density functional theory. Spin-splitting and spin-degenerate bands are realized in Ti-, V-, Cr-, Mn-, Fe-, and Co- and Sc-, Ni-, Cu-, and Zn-adsorbed systems, respectively. Especially, the reemergence of the electron–hole pockets appears in the Ni-adsorbed system. The calculated results are robust against inclusion of spin–orbit coupling and Coulomb interaction.